PENGARUH TERAPI RELAKSASI AUTOGENIK TERHADAP PENURUNAN TEKANAN DARAH SISTOLIK PADA LANSIA DENGAN HIPERTENSI DI RW 005 WILAYAH KERJA PUSKESMAS SINDANGKERTABANDUNG BARAT 2025 - D, Ripaldi; MS, Haryanto (SINERGI : Jurnal Riset Ilmiah, 2025)
Elderly people are closely related to hypertension, elderly people experience increased blood pressure related to the elasticity of blood vessels. Hypertension is a condition of systolic >140 mmHg and diastolic >90 mmHg. The purpose of this study was to determine the effect of autogenic relaxation therapy on reducing systolic blood pressure in elderly people in RW 005. Quasi-experimental method with a pre and post-test non-equivalent control group design approach, with 50 respondents and quota sampling technique. Analysis using the Wilcoxon Test. Continued statistical test Mann Whitney U Test to identify differences in blood pressure between the intervention group and the control group. The results of the analysis obtained a median systolic blood pressure value of 140, a minimum value of 130, a maximum value of 160 before the intervention. The results of the analysis of 25 elderly people obtained a median systolic blood pressure value of 130, a minimum value of 110, a maximum value of 150 after the autogenic relaxation intervention. The results of the analysis of 25 elderly people obtained a median systolic blood pressure value of 140, a minimum value of 130, a maximum value of 180 in the control group of the initial examination. The results of the analysis of 25 elderly people obtained a median systolic blood pressure value of 140, a value of 130, and a maximum value of 180 in the control group of the final examination. There is a difference in systolic blood pressure in the treatment group before and after being given autogenic relaxation therapy with a p value of 0.001. There is no difference in initial and final systolic blood pressure in the control group with a p value of 0.180. There is a difference in systolic blood pressure in the treatment group and the control group with a p value of <0.05